Soundscapes and Emotional Experiences in World Heritage Temples: Implications for Religious Architectural Design - Yanling Li; Xiaocong Li; Ming Gao (Buildings)
The impact of soundscapes in religious architecture on public psychology has garnered increasing attention in both research and policy domains. However, the mechanisms by which temple soundscapes influence public emotions remain scientifically unclear. This paper aims to explore how soundscapes in temple architectures designated as World Natural and Cultural Heritage sites affect visitors’ experiences. Considering visitors with diverse social and demographic backgrounds, the research design includes subjective soundscape evaluations and EEG measurements from 193 visitors at two World Heritage temples. The results indicate that visitors’ religious beliefs primarily affect their soundscape perception, while their soundscape preferences show specific correlations with chanting and human voices. Furthermore, compared to males, females exhibit greater sensitivity to emotional variations induced by soundscape experiences. Urban architects can enhance visitors’ positive emotional experiences by integrating soundscape design into the planning of future religious architectures, thereby creating pleasant acoustic environments.